LncRNA-RMST Functions as a Transcriptional Co-regulator of SOX2 to Regulate miR-1251 in the Progression of Hirschsprung's Disease - Zhou, Lingling; Zhi, Zhengke; Chen, Pingfa; Du, Chunxia; Wang, Binyu; Fang, Xiang; Tang, Weibing; Li, Hongxing (Frontiers in Pediatrics, 2022)
Hirschsprung’s disease (HSCR) is a congenital disorder characterized by the absence of enteric neural crest cells (ENCCs). LncRNA Rhabdomyosarcoma 2-associated transcript (RMST) is essential for the growth and development of neuron. This study aimed to reveal the role of RMST in the pathogenesis of HSCR. The expression level of RMST, miR-1251, SOX2 and AHNAK.was evaluated with qRT-PCR or western blot. CCK-8 and transwell assays were applied to detect cell proliferation and migration. CHIP and RIP assays were applied to determine the combination relationship between SOX2 and promoter region of miR-1251 or RMST and SOX2, respectively. Dul-luciferase reporter assay was performed to confirm miR-1251 targeted AHNAK. As results shown, RMST was down-regulated in the aganglionic colon of HSCR patients. The knockdown of RMST attenuated cell proliferation and migration significantly. MiR-1251, the intronic miRNA of RMST, was also low-expressed in HSCR, but RMST did not alter the expression of miR-1251 directly. Furthermore, SOX2 was found to regulate the expression of miR-1251 via binding to the promoter region of miR-1251, and RMST strengthened this function by interacting with SOX2. Moreover, AHNAK was the target gene of miR-1251 which was co-regulated by RMST and SOX2. In conclusion, our study demonstrated that RMST functioned as a transcriptional co-regulator of SOX2 to regulate miR-1251 and resulted in the upregulation of AHNAK, leading to the occurrence of HSCR. The novel RMST/SOX2/miR-1251/AHNAK axis provided potential targets for the diagnosis and treatment of HSCR during embryonic stage.